Midterm results of endoscopically assisted first rib resection in the zero position for thoracic outlet syndrome. (12th September 2022) - Satake, Hiroshi; Honma, Ryusuke; Nito, Toshiya; Naganuma, Yasushi; Shibuya, Junichiro; Maruyama, Masahiro; Uno, Tomohiro; Takagi, Michiaki
Abstract: OBJECTIVES: We have hypothesized that an endoscopically assisted transaxillary approach in the zero position would be able to improve visualization and allow safe surgery for thoracic outlet syndrome. METHODS: We performed surgery only for patients with certain objective findings, including blood flow disruption, low blood flow and accelerated blood flow in the subclavian artery demonstrated using Doppler sonography, narrowing of the scalene interval width between the anterior and middle interscalene muscles (interscalene base) or costoclavicular space demonstrated using Duplex ultrasonography or computed tomography angiography. The present study included 45 consecutive patients (50 limbs) who underwent endoscopic transaxillary first rib resection with scalenotomy and brachial plexus neurolysis. We assessed the intraoperative parameters, including the interscalene base, blood loss, operation time, patient satisfaction, preoperative and postoperative Quick Disability of the Arm, Shoulder and Hand and complications. RESULTS: The mean intraoperatively measured interscalene base width was 6.4 mm. All patients showed improvement after surgery. The outcome was excellent in 40% of cases, good in 48%, fair in 12% and poor in none. Pneumothorax was present in 6%. There were no other complications and no recurrences. Among patients who had been followed up for at least 2 years, the Quick Disability of the Arm, Shoulder and Hand score was significantly improved (42 before surgery vs 12 at final follow-up), especially in athletes relative to non-athletes (0.2 vs 16). The present approach achieved complete relief in 43% of cases overall (91% in athletes and 16% in non-athletes). CONCLUSIONS: Endoscopically assisted transaxillary first rib resection and brachial plexus neurolysis in the zero position are useful and safe for thoracic outlet syndrome, especially in athletes. Abstract : The diagnosis of thoracic outlet syndrome (TOS) is controversial, and no specific set of diagnostic criteria has yet been established [1].